Self-employment in Hungarian law - Tamás, Gyulavári (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
Self-employment has traditionally been regulated by the Civil Code, as a distinctive form of work apart from employment. This chapter strives to evaluate the labour law framework and labour market experience of self-employment. First, the Hungarian legal provisions on self-employment will be highlighted, including labour law, civil law and social security law. This will be followed by an evaluation of the available data on labour market trends regarding the various groups of self-employed workers, such as genuine and false self-employment, and economically dependent work. After this summary on employment data, the legal protection or scope of employee rights enjoyed by self-employed persons will be scrutinised. Finally, I will examine the Hungarian legal mechanisms to combat false self-employment. As a whole, the paper will provide a picture of the legal environment of self-employment with laws, trends and some evident flaws. I will strive to highlight the main driving forces behind self-employment and related labour law policy.